2017
DOI: 10.5296/ijhrs.v7i4.11977
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relation between the Demographics of Human Resource Managers in Turkey and Characteristics of their Companies

Abstract: The demographics of HR managers have been a matter of discussion for a long time. Most frequently encountered comments include; those that work in the field of HRM are generally female, those that have a Bachelor's Degree in business administration or economics, psychology, the humanities or law and those that have Master's Degree, have more work experience or those that are transferred from other companies are mostly employed in HRM. A more in-depth analysis may be obtained by the comparing the demographics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, HR managers working in Turkey are mainly male. However, Demir and Uyargil (2017) find that more than half of the HR managers are female, and great majority of HR managers hold Bachelor's Degree. Business administration is the most common field in Bachelor's Degree.…”
Section: Demographics Of Turkish Hrmentioning
confidence: 96%
“…On the other hand, HR managers working in Turkey are mainly male. However, Demir and Uyargil (2017) find that more than half of the HR managers are female, and great majority of HR managers hold Bachelor's Degree. Business administration is the most common field in Bachelor's Degree.…”
Section: Demographics Of Turkish Hrmentioning
confidence: 96%
“…e results showed that the demographic characteristics of employees are effective in reducing turnover intention. Demir and Uyargil [15] examined the relationship between employee demographic characteristics and the choice of human resource management methods.…”
Section: Research Literature: Job Leaving Demographic Effects Choice ...mentioning
confidence: 99%